NON - SENS OU BON SENS? FLOIRE ET BLANCHEFLEUR, UNE IDYLLE SANGLANTE - Brînduşa Grigoriu (Anastasis: Research in Medieval Culture and Art, 2017)
To a modern reader, Robert d’Orbigny’s romance is probably one of the most challenging idylls of the Middle Ages: the young beautiful heroes Floire and Blanchefleur, happily married and ready to found a Christian family (and conceive Berthe, Charlemagne’s mother), become, in two verses at the end of the romance, the proficient perpetrators of genocide (ms. A, v. 3331-3332). Converted through love and empathy, as soon as he is proclaimed Spain’s king, Floire completes a mass conversion through crime and baptism, moved by his tender feelings for Blanchefleur. Jean-Luc Leclanche, editor of the “aristocratic” version of the text, insists on the banality of this form of conversion at that time, and presents the Conte as a pacifist sample of clerical writing. Our paper invites to a new interpretation of this widely circulated story, exploring the emerging ideology of happy ending stories through the concept of “emotional intelligence”.